Una visión global de la filosofía de Francisco Leocata - Zanotti, Gabriel J. (Sapientia, 2022)
The aim of this article is to provide a general overview of the philosophy of Father Francisco Leocata in such a way that the reader can appreciate its essential significance for the dialogue of Christianity with the contemporary world.